Clinical and Biomechanical Aspects of Removable Partial Dentures in Patients with Partial Tooth Loss - Abdukhamidov Juraber Laziz ugli; Akhmedov Alisher Astanovich (American Journal of Biomedicine and Pharmacy, 2025)
This article provides a comprehensive overview of the clinical and biomechanical principles underlying the design, fabrication, and maintenance of removable partial dentures (RPDs) in partially edentulous patients. It emphasizes the role of biomechanical analysis in achieving stability, retention, and stress distribution to preserve remaining oral structures. The study discusses key clinical considerations such as abutment tooth selection, clasp design, major connector configuration, and occlusal balance, which together determine prosthesis performance and patient comfort. The biological impact of RPDs on oral tissues, potential complications such as tissue irritation, abutment overload, and bone resorption, as well as strategies for their prevention, are thoroughly examined. Integrating modern materials and digital design approaches, the research highlights current innovations aimed at improving functionality, esthetics, and longevity of removable partial dentures in prosthodontic practice. This article explores the clinical and biomechanical foundations of removable partial dentures (RPDs) in managing partial edentulism, emphasizing how appropriate design, material selection, and load distribution determine long-term success. It provides a detailed assessment of how RPDs interact with oral tissues and abutment teeth to restore function and esthetics while preserving remaining structures. The research focuses on analyzing stress transmission, support mechanics, and the influence of occlusal forces on the prosthesis and underlying tissues. It also examines the challenges encountered in clinical practice, including abutment overload, mucosal irritation, and ridge resorption, alongside preventive strategies. Recent technological advancements such as CAD/CAM fabrication, digital modeling, and flexible materials are discussed for their potential to improve precision, comfort, and biomechanical performance.